Clinical Efficacy of Azithromycin Versus Ciprofloxacin in Treatment of Typhoid Fever in Children - Sohaib Riaz, Ghulam Hussain, Zeeshan Javed, Nadeem Yaqoob, Saima Rasheed, Nadia Safir, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the clinical efficacy of Azithromycin with ciprofloxacin in treatment of typhoid fever in children. Methodology: After permission from hospital ethical committee (letter attached) and informed written consent taken from attendants of patients of inclusion criteria, data was collected on data collection Performa. Patients fulfilling the criteria were admitted in Paediatric Department, Dar-ul-sehat hospital, Faisalabad. Patients were divided by lottery method into two groups A and B. Group A was given ciprofloxacin 15mg/kg/dose BD orally for 7 days. Group B was given azithromycin 10mg/kg/dose OD orally for 7 days. Both groups were kept under close observation for 7 days. Monitoring of patient during stay was done by researcher. The cost of medicine was beard by hospital. Results: In our study, 65%(n=65) in Cipro group and 52%(n=52) in Azithro group were between 3-8 years of age while 35%(n=35) in Cipro group and 48%(n=48) in Azithro group were between 9-14 years of age, mean+sd was calculated as 7.07+3.25 and 8.27+3.03 years respectively, 48%(n=48) in Cipro group and 55%(n=55) in Azithro group were male while 52%(n=52) in Cipro group and 45%(n=45) in Azithro group were females. Comparison of efficacy of oral azithromycin versus Ciprofloxacin in children with enteric fever shows that 72%(n=72) in Cipro group and 85%(n=85) in Azithro group were treated effectively, p value was calculated as 0.02 showing a significant difference. Conclusion: We concluded that the clinical efficacy of Azithromycin is significantly higher when compared with ciprofloxacin in treatment of typhoid fever in children. Keywords: Children, Typhoid fever, treatment, Azithromycin, ciprofloxacin.